KLHL6 is a tumor suppressor gene in diffuse large B-cell lymphoma. Issue 3 (1st February 2019) - Choi, Jaewoo; Zhou, Nan; Busino, Luca
ABSTRACT: The ubiquitin proteasome system (UPS) plays a critical function in cellular homeostasis. The misregulation of UPS is often found in human diseases, including cancer. Kelch-like protein 6 (KLHL6) is an E3 ligase gene mutated in diffused large B-cell lymphoma (DLBCL). This review discusses the function of KLHL6 as a cullin3-RING ligase and how cancer-associated mutations disrupt the interaction with the cullin3, resulting in the loss of KLHL6 function. Furthermore, the mRNA decay factor Roquin2 is discussed as the first bona fide substrate of KLHL6 in the context of B-cell receptor activation and B-cell lymphoma. Importantly, the tumor-suppressing mechanism of KLHL6 via the degradation of Roquin2 and the mRNA decay in the context of the NF-κB pathway is summarized.